Ternary Hybrid γ‐Fe2O3/CrVI/Amine Oxidase Nanostructure for Electrochemical Sensing: Application for Polyamine Detection in Tumor Tissue. Issue 20 (8th April 2016) - Bonaiuto, Emanuela; Magro, Massimiliano; Baratella, Davide; Jakubec, Petr; Sconcerle, Elisabetta; Terzo, Milo; Miotto, Giovanni; Macone, Alberto; Agostinelli, Enzo; Fasolato, Silvano; Venerando, Rina; Salviulo, Gabriella; et al.
Abstract: Dichromate binds to surface‐active maghemite nanoparticles (SAMNs) to form a stable core–shell nanostructures (SAMN@Cr VI ). The hybrid was characterized by Mössbauer spectroscopy, high‐angle annular dark‐field imaging, electron energy‐loss spectroscopy, and electrochemical techniques, which revealed a strong interaction of dichromate with the nanoparticle surface. Electrochemical characterization showed lower charge‐transfer resistance, better electrochemical performance, and more reversible electrochemical behavior with respect to naked SAMNs. Moreover, SAMN@Cr VI is an excellent electrocatalyst for hydrogen peroxide reduction. Furthermore, an enzyme, namely, bovine serum amine oxidase (BSAO: EC 1.4.3.6), was immobilized on SAMN@Cr VI by self‐assembly to give a ternary hybrid nanostructured catalyst for polyamine oxidation (SAMN@Cr VI ‐BSAO). SAMN@Cr VI ‐BSAO was applied for the development of a reagentless, fast, inexpensive, and interference‐free polyamine biosensor, which was successfully exploited for the discrimination of tumorous tissue from healthy tissue in human crude liver extracts. Abstract : Polyamine detector : Dichromate binds to surface‐active maghemite nanoparticles (SAMN) to form a stable core–shell nanostructure (SAMN@Cr VI ), which is an excellent electrocatalyst for hydrogen peroxide reduction. Bovine serum amine oxidase was immobilized on SAMN@Cr VI to give a ternary hybrid nanostructured catalyst for polyamine oxidation, which was used to develop a reagentless, fast, inexpensive, and interference‐free polyamine biosensor for the discrimination of tumor tissue from healthy tissue in human crude liver extracts (see figure).